The Socio-Economic Contribution of Muʾlft qulub and Fi sabilillah Zakat: Contemporary Applications in Sri Lanka - Jiffry, Arafath Careem (International Journal of Islamic Economics and Finance (IJIEF), 2024)
The zakat obligation mandates Muslims with surplus wealth to donate to specific beneficiaries. In Sri Lankan zakat jurisprudence, Muʾlft qulub is narrowly interpreted to include only recent converts to Islam, while Fi sabilillah is limited to warriors fighting for Islam. This interpretation follows the Shafiʿi school of thought, which advises against distributing zakat to non-Muslims or to righteous individuals broadly. This restrictive approach undermines the broader objectives of zakat, such as promoting social justice, reducing poverty, enhancing welfare, ensuring economic stability, and fostering inter- and intra-community relationships. The paper employs a qualitative content analysis methodology alongside a Muslim minority fiqh approach to connect Islamic principles with the socio-economic context of the Sri Lankan Muslim minority. It argues that the classical jurisprudential interpretation is inadequate for addressing the unique challenges of the modern Sri Lankan socio-economic environment. By applying a fiqh of the Muslim minority approach, the paper suggests a moderate expansion of the Muʾlft qulub and Fi sabilillah categories. This expansion would help achieve the broader socio-economic goals of zakat and empower the Muslim community in Sri Lanka.